The Diliman review (Quezon City, Philippines : College of Liberal Arts, University of the Philippines, 1953)
'Devoted to letters, the arts and discussion.'
Title from cover.
In English 1953- ; in Tagalog <1990- >
Keywords: Philippines -- Intellectual life -- Periodicals